Regulating non-precious transition metal nitrides bifunctional electrocatalysts through surface/interface nanoengineering for air-cathodes of Zn-air batteries - Du, Qixing; Gong, Yanmei; Khan, Muhammad Arif; Ye, Daixin; Fang, Jianhui; Zhao, Hongbin; Zhang, Jiujun (Green energy & environment, 2022)
Zn-air batteries (ZABs), especially the secondary batteries, have engrossed a great interest because of its high specific energy, economical and high safety. However, due to the insufficient activity and stability of bifunctional electrocatalysts for air-cathode oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) processes, the practical application of rechargeable ZABs is seriously hindered. In the effort of developing high active, stable and cost-effective electrocatalysts, transition metal nitrides (TMNs) have been regarded as the candidates due to their high conductivity, strong corrosion-resistance, and bifunctional catalytic performance. In this paper, the research progress in TMNs-based material as ORR and OER electrocatalysts for ZABs is discussed with respect to their synthesis, chemical/physical characterization, and performance validation/optimization. The surface/interface nanoengineering strategies such as defect engineering, support binding, heteroatom introduction, crystal plane orientation, interface construction and small size effect, the physical and chemical properties of TMNs-based electrocatalysts are emphasized with respect to their structures/morphologies, composition, electrical conductivity, specific surface area, chemical stability and corrosion resistance. The challenges of TMNs-based materials as bifunctional air-cathode electrocatalysts in practical application are evaluated, and numerous research guidelines to solve these problems are put forward for facilitating further research and development. This review summarizes the progress of transition metal nitrides modified by surface/interface nanoengineering strategies such as defect engineering, support binding and heteroatom introduction as air-cathodes catalysts for Zn-air batteries. [Display omitted]